Selective attention and the importance of types for information campaigns - Maria Perrotta Berlin; Benjamin Mandl (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2020)
In this paper we try to contribute to the understanding of the persistence and increase of meat eating in the face of mounting evidence on the ills of meat production and consumption by considering the role of selective attention and learning. We aim to test whether agent type plays a role in this process. If this hypothesis is true, simple informational campaigns about the externalities of meat consumption might be ineffective as the informational content may be lost on precisely the population of interest, omnivores. Policy strategies to reach this goal would then need to be refined. Our conclusions apply more generally to a policy agenda for climate-change curbing action, an area where convergence to nudges or strong incentives is proving very hard for policy makers at all levels, and the potential for information to spark action on its own would be very valuable.
Keywords: Q00; 330; meat consumption; meat production; meat industry